Feasibility of probing the NEEC process using storage rings - Yang, Yi; Wang, Yumiao; Ma, Zhiguo; Fu, Changbo; He, Wanbing; Ma, Yugang (Frontiers in Physics, 2024)
One of the fundamental processes in nuclear physics is nuclear excitation by electron capture (NEEC). Having been proposed theoretically for almost 50 years, the experimental confirmation of NEEC is still missing, making it imperative to validate this process. In this paper, we propose a new experimental method based on the anti-coincidence principle to search for the long-anticipated NEEC phenomenon, which involve heavy-ion storage rings. Our calculations indicate that the proposed experimental setup, storage ring, have the potential to surmount background noise, particularly Radiative Recombination (RR) and Coulomb Excitation (CE), and offer a high likelihood of discovering the long-awaited NEEC process.